2011
DOI: 10.1016/j.avsg.2010.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Genes and Abdominal Aortic Aneurysm

Abstract: Abdominal aortic aneurysm (AAA) is a multifactorial disease with a strong genetic component. Since first candidate gene studies were published 20 years ago, nearly 100 genetic association studies using single nucleotide polymorphisms (SNPs) in biologically relevant genes have been reported on AAA. The studies investigated SNPs in genes of the extracellular matrix, the cardiovascular system, the immune system, and signaling pathways. Very few studies were large enough to draw firm conclusions and very few resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 210 publications
(245 reference statements)
1
62
0
Order By: Relevance
“…About 10–20% of AAA patients have at least one relative with this condition and formal segregation analyses have favored genetic models in explaining this familial aggregation [21,38,39,83]. The Swedish Twin registry, which contains data on all 172,890 twins born in Sweden since 1886, has 265 twins with an AAA [80].…”
Section: Aaa As a Complex Genetic Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…About 10–20% of AAA patients have at least one relative with this condition and formal segregation analyses have favored genetic models in explaining this familial aggregation [21,38,39,83]. The Swedish Twin registry, which contains data on all 172,890 twins born in Sweden since 1886, has 265 twins with an AAA [80].…”
Section: Aaa As a Complex Genetic Diseasementioning
confidence: 99%
“…Since the first candidate gene studies were published more than 20 years ago, over 100 genetic association studies using single nucleotide polymorphisms (SNPs) in biologically relevant genes have been reported on AAA [83]. More recently, unbiased genome-wide approaches such as family-based DNA linkage studies and genome-wide association studies (GWAS) have been carried out to identify susceptibility loci for AAA.…”
Section: Aaa As a Complex Genetic Diseasementioning
confidence: 99%
“…Overall, only a small minority of the candidate gene-association studies (more than 100 studies analysing several functional and non-functional SNPs) published to date were sufficiently powered to draw firm conclusions and very few results could be replicated in different sample sets. Hinterseher et al32 provide an exhaustive review of all data available until recently (2011) regarding associations between specific SNPs and AAA presence in various populations. They have identified various associations of some significance, but the vast majority of the studies included have analysed populations of less than 150 individuals.…”
Section: Genetic Studiesmentioning
confidence: 99%
“…Three genome-wide association studies have individually identified three novel single nucleotide polymorphisms (SNPs) associated with AAA 5. These SNPs, however, account for only a small proportion of AAA heritability 6. Improved knowledge of the genetically determined susceptibility to AAA may provide insight into novel pharmacological targets for this condition and assist targeted population-based screening programmes.…”
Section: Introductionmentioning
confidence: 99%